(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The orographic precipitation pattern is one of the most prominent in the mountainous region of Lattakia governorate, highlighting the role of terrain in maximizing the role of convectional and cyclonic rains leading to heavy precipitation compared to the celestial and plateau areas, so the research aims to analyze the distribution and spatial and temporal variability of the orographic precipitation. (Formed and enhanced by terrain) during the 1990-2020 climatic cycle through the use of statistical and cartographic methods. The research concluded that the increase in topographic elevation is 73% responsible for the increase in average precipitation and is the primary responsible for decreasing temperature, increasing relative humidity and atmospheric instability in the studied area The orographic enhancement average is 1.06 per 200m, and the greatest enhancement is concentrated at altitudes of 1001-1200m for the overall average and the spring average. In winter, the greatest enhancement is concentrated at 601-800m and in autumn at the level of 801-1000. Higher terrain floors are passively enhanced due to the discharge of the content of the rising masses of moisture at lower levels.